ANALISA DAMPAK RISIKO KREDIT, RISIKO LIKUIDITAS DAN EFISIENSI OPERASIONAL TERHADAP RETURN ON ASSET PADA BANK UMUM KONVENSIONAL SELAMA PERIODE 2016-2020 - Iman Tri Haryanto; Muchlis Muchlis (Ibs Press, 2023)
This research is performed in order to test the influence of the variable Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) and BOPO toward Return on Asset (ROA). Sampling technique used is purposive sampling with criteria as General Banking in Indonesia who provide financial report and traded during period 2016 through 2020. The Data is based on annual report conventional bank period 2016 to 2020. Obtained by amount sampel as much 65 company from 92 conventional banking company in Indonesia 2016-2020 period. Analysis technique used is multiple linear regression and hypothesis test use t-statistic to test coefficient of regression partial and also f-statistic to test the truth of collectively influence in level of significance 5%. Others also done a classic assumption test covering normality test, multicolinierity test, heteroscedastisity test and autocorrelation test. During research period show as data research was normally distributed. Based on multicolinierity test, heteroscedasticity test and autocorrelation test variable digressing of classic assumption has not founded, its indicate that the available data has fulfill the condition to use multi linier regression model. From the result of analyse indicate that data NPL, LDR and BOPO in partial significant toward ROA conventional bank period 2016-2019 at level of significant less than 5%. Meanwhile data conventional bank period 2016-2020 NPL and BOPO in partial significant toward ROA, but LDR not significant at level of significant less than 5%.